The Effect of Transformational Leadership and Organizational Culture on Civil Servants’ Performance: The Mediating Role of Organizational Citizenship Behavior (A Study at the Regional Secretariat of Padang Pariaman Regency) - Hanifah, Zarma; Syamsir, Syamsir (JESS (Journal of Education on Social Science); Vol 10 No 1 (2026): Public Service and GovernanceDO - 10.24036/jess.v10i1.649, 2026)
The performance of Civil Servants (Aparatur Sipil Negara/ASN) is a crucial determinant of effective public administration, particularly in regional institutions that function as policy coordination centers. However, fluctuations in organizational performance indicated that formal performance management systems alone were insufficient to ensure consistent outcomes. This study aimed to analyze the effects of transformational leadership and organizational culture on ASN performance, with Organizational Citizenship Behavior (OCB) as a mediating variable. The research employed a quantitative explanatory approach involving 103 civil servants at the Regional Secretariat of Padang Pariaman Regency, selected through proportional stratified random sampling. Data were collected using a structured questionnaire measured on a Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results showed that transformational leadership and organizational culture had positive and significant effects on OCB and ASN performance. Furthermore, OCB had the strongest and most significant influence on ASN performance and effectively mediates the relationship between transformational leadership, organizational culture, and performance. These findings indicated that improving ASN performance required not only structural and formal mechanisms, but also the strengthening of voluntary work behavior fostered by effective leadership and a supportive organizational culture.